INTEGRATION OF TECHNOLOGY AND NATURAL SCIENCES (IN THE CASE OF P78RIMARY EDUCATION) - Salokhitdinova, Navruza Murodulla kizi (Innovative Development in Educational Activities, 2023)
This article describes the interdisciplinary relationship between technology and natural sciences in primary education. That is, it explains how technology and natural science enter into an integrative process with each other. Naturally, there are many technical and technological problems in production, and without their elimination it is impossible to increase production efficiency. This process certainly shows the connection of the natural sciences.